Heat transfer, tribology and performance of graphene nanolubricants in an IC engine - Rasheed, Abdul Khaliq (2017)
Improving the thermo-physical and tribological properties of lubricants has been a challenging subject of research. Over the last few years, nanolubricants, which are oils containing nanoparticle have been reported to possess exceptionally higher thermal and tribological properties than the traditional lubricants. However, nanolubricants complying with the American Petroleum Institute (API) and Society of Automotive Engineers (SAE) standards remain largely unexplored. In this dissertation, graphene based automotive lubricants meeting 20W50 API SN/CF and 20W50 API SJ/CF specifications have been investigated using a wide range of analytical methods. Thermal-physical and tribological properties have been thoroughly studied. A four-stroke IC engine test rig has been fabricated to investigate the performance of the formulated nanolubricant. By adding 0.01 wt% of 60 nm graphene and 1% lubricity additive to 20W50 API SN/CF oil, 21% and 23% enhancement in the coefficient of friction (µ) and thermal conductivity (k) at 80°C respectively was observed. Viscosity of SNCF with 0.01 wt% of 60 nm graphene and 1% lubricity increases by ~6% at 25°C, and ~9% at 105°C. Scanning electron microscopy and Energy-dispersive X-ray spectroscopy suggest that many nano-tribo mechanisms occurring simultaneously or subsequently could be the reason for enhanced anti-wear and antifriction behaviour of the nanolubricant. Graphene found in the used engine oil indicates that the multilayer graphene exfoliates, rolls up to become helical coils or tube like structure and subsequently entangles with other flakes. As a result, gradually augmenting the thermal performance of the oil. Thermogravimetric analysis revealed that the onset temperature of oxidation for the SN/CF oil could be delayed by 13-17 °C in the presence of graphene. Moreover, the rate of oxidation when the weight loss of oil in the presence of graphene reaches 40% to 20% could be delayed by more than 30 °C. Resistance to oil degradation depends strongly on the graphene nanoparticle size and concentration. TGA kinetics studies show that the base oils have higher activation energy (Ea) and the addition of graphene significantly reduces Ea. Furthermore, 70% enhancement in heat transfer rate is also achieved in the presence of graphene. SEM images of the piston rings collected after 100 hours of engine operation show that the oil containing graphene (12 nm) decreases the piston wear compared to base oil without graphene. Elemental analysis indicates that the addition of a natural polymeric ester based lubricity additive helps even the graphene of highest thickness to perform better in boundary lubrication conditions.